Microorganisms in soils : (Springer, 2005)
Soils would not exist without the complex and heterogeneous activities of microorganisms. For the third volume of Soil Biology, an international board of renowned scientists shed light on the significant role of these organisms. The following key topics are covered: Microorganisms in bioerosion, humification, mineralization and soil aggregation; Microbial energetics and microbes in biogeochemical processes such as carbon and nitrogen cycles and phosphorus bio-availability; Interactions in the mycorrhizosphere, e.g. between mycorrhizal fungi and bacteria; Impact of microbes on plant nutrient cycling and the possible effects of transgenic rhizospheres on soil fungi; Functions of microbes in specific soil compartments such as soil surface or toxic metal polluted soils; Regulation of microbial activities in functional domains that are influenced by biotic or abiotic factors; Use of marker genes and isotopes as examples for modern techniques in soil microbiology.